Analytic Network Process on Early Warning Indicators for Financial System Stability - Rani, Lina Nugraha; Hasib, Fatin Fadhilah (Islamic Economics Methodology, 2024)
The purpose of this research is to find out the leading indicators of financial crisis from the perspective of expert practitioners, micro and macroeconomic sides; Based on the results of interviews with banking practitioner experts, related to the most important indicators of financial system stability in Indonesia, both microprudential and macroprudential criteria, both aspects are equally considered important and priority. However, from the practitioners' perspective, the microprudential aspect is a more important factor (0.506) than the macroprudential aspect (0.494). Macroprudential and Microprudential policies issued by Bank Indonesia as the central bank with full authority play an important role in maintaining Financial System Stability. The presence of the Financial System Stability Coordination Forum (FKSSK) which consists of several financial authorities is expected to be able to save the economic conditions of the Indonesian nation in the financial sector. For future research, this study is expected to be an initial step. For example, by further expanding the number of expert respondents who are not only from banking practitioners, but also from academics and policy makers.